Potential Utilization of Microcystis sp. for Biodiesel Production - Madusnnka, D.A.T.; Manage, P.M. (Environment and Natural Resources Journal, 2016)
Atached
Keywords: Microcystis bloom; Fatty acid methyl esters; Biodiesel B6 blend; Energy crisis